2019
DOI: 10.1016/j.jtho.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Response to the Letter to the Editor: Lung Immune Prognostic Index for Outcome Prediction to Immunotherapy in Patients With NSCLC

Abstract: Phase II trial of atezolizumab as first-line or subsequent therapy for patients with programmed death-ligand 1-selected advanced non-small-cell lung cancer (BIRCH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…For example, the estimated absolute benefit in median PFS for ABCP (compared to BCP) was 3 months in the good LIPI group with no observed benefit in the poor LIPI group. The estimated decrease in OS and PFS benefit in the poor LIPI group did not constitute a statistically significant interaction, which is consistent with prior studies demonstrating that LIPI is also a prognostic marker for traditional chemotherapy options [8,14,15,21,22]. Nonetheless, it is recognized that clinical trials are not typically powered to detected treatment-by-covariate interactions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, the estimated absolute benefit in median PFS for ABCP (compared to BCP) was 3 months in the good LIPI group with no observed benefit in the poor LIPI group. The estimated decrease in OS and PFS benefit in the poor LIPI group did not constitute a statistically significant interaction, which is consistent with prior studies demonstrating that LIPI is also a prognostic marker for traditional chemotherapy options [8,14,15,21,22]. Nonetheless, it is recognized that clinical trials are not typically powered to detected treatment-by-covariate interactions.…”
Section: Discussionsupporting
confidence: 85%
“…Studies have also demonstrated that LIPI may differentiate prognosis in patients treated with ICIs in other cancer types, including breast cancer, hepatocellular carcinoma, melanoma, renal cell carcinoma, small cell lung cancer, and urothelial carcinoma [12,[17][18][19][20]. In addition to behaving as a prognostic biomarker, LIPI has been proposed as a method to classify patients subgroups with disparities in ICI treatment efficacy (i.e., a predictive biomarker) [13], albeit findings have been conflicting [8,14,15,21,22]. To date, there is minimal information of the prognostic performance of LIPI in patients with NSCLC initiating first-line, combination ICI approaches [11,12], and there is no information on treatment efficacy across LIPI defined subgroups in this cohort.…”
Section: Introductionmentioning
confidence: 99%